2017
DOI: 10.1111/andr.12391
|View full text |Cite
|
Sign up to set email alerts
|

Are incident gallstones associated to sex‐dependent changes with age? A cohort study

Abstract: Age and female sex have repeatedly been identified as gallstone determinants but the underlying mechanisms are not clarified. The objectives of this study were to determine if changes with age in physiology, lifestyle, or reproductive hormones were associated with incident gallstones. A cohort study of a general population random sample (N = 2366) aged 30-60 years was performed. Participants were ultrasound screened for gallstones in 1982-84 and again in 1993-94. Lifestyle data and blood samples were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…In contrast to the predilection of women for cholecystectomy based on a hospitalization database from the United States, our findings were consistent with a hospitalization-based study conducted in Japan and Taiwan to demonstrate that most patients undergoing cholecystectomy were men [21,22]. Furthermore, the findings with the predisposition of patients aged ≥ 50 years to cholecystectomy were consistent with the liability of the elderly to GBS due to increased biliary cholesterol secretion, impaired bile salt synthesis, poor gallbladder contractility, and increased exposure to pro-lithogenic factors [23,24]. Whereas most individuals with cholecystectomy belonged to the occupation category of a blue collar occupation (52.6%) and lived in the least urbanized area (33.6%), which might be due to the relatively unhealthy lifestyle behaviors [25].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to the predilection of women for cholecystectomy based on a hospitalization database from the United States, our findings were consistent with a hospitalization-based study conducted in Japan and Taiwan to demonstrate that most patients undergoing cholecystectomy were men [21,22]. Furthermore, the findings with the predisposition of patients aged ≥ 50 years to cholecystectomy were consistent with the liability of the elderly to GBS due to increased biliary cholesterol secretion, impaired bile salt synthesis, poor gallbladder contractility, and increased exposure to pro-lithogenic factors [23,24]. Whereas most individuals with cholecystectomy belonged to the occupation category of a blue collar occupation (52.6%) and lived in the least urbanized area (33.6%), which might be due to the relatively unhealthy lifestyle behaviors [25].…”
Section: Discussionsupporting
confidence: 88%
“…15 Consumption of alcohol found to be inversely associated with GSD in females as well as males but it was statistically insignificant, this has been corroborated with other studies, whereas some studies showed that alcohol not associated with GSD in males and inversely associated in females. [18][19][20] Sedentary life style was found to be significant risk factor for the development of GSD in both the sexes, this has been corroborated with other studies, whereas Sun et al found no significant association neither in females nor in males. 4,6,7,18 High BMI and high waist hip ratio were significantly associated with development of GSD in females same results were seen in other studies; but in males we have found no association, whereas as several studies found significant association.…”
Section: Discussionsupporting
confidence: 70%
“…Age and BMI are also independent determinants of gallstones [ 6 , 8 , 9 , 27 , 45 , 46 , 52 58 ]. Other reported risk factors for gallstones are family history [ 6 ], abnormal liver function tests including high bilirubin, AST, and ALT [ 54 56 , 59 ], and abnormal lipoprotein levels including low HDL-C, high LDL-C, and triglycerides [ 46 , 58 , 60 ].…”
Section: Discussionmentioning
confidence: 99%